Mineral-based photo-thermal composite hydrogel as well as preparation method and application thereof

By introducing ZIF-67 derived porous carbon/montmorillonite composite materials into the composite photothermal hydrogel, the existing composite photothermal hydrogels have solved the problems of low intensity, low light absorption, low evaporation rate and high evaporation enthalpy value, and efficient photothermal conversion and seawater desalination and desalination capabilities.

CN119798768AActive Publication Date: 2025-04-11CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510007300.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing composite photothermal hydrogels have problems such as low intensity, low light absorption, low evaporation rate and high evaporation enthalpy, which is difficult to meet the efficient needs of seawater desalination and sewage treatment.

Method used

The ZIF-67-derived porous carbon/montmorillonite composite material was used to combine with polyvinyl alcohol and chitosan to prepare mineral-based photothermal composite hydrogels through physical cycle freezing-thawing method to improve their photothermal conversion ability and mechanical strength.

Benefits of technology

It realizes efficient photothermal conversion, with the absorbance exceeding 90% within the full spectrum range, the water evaporation rate can reach 2.2kg m-2h-1, and the desalination capacity exceeding 98%, and the mechanical strength and structural stability of the hydrogel are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798768A_ABST
    Figure CN119798768A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel, in particular to mineral-based photo-thermal composite hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, growing ZIF-67 particles on the surface of montmorillonite in situ; calcining and carbonizing to obtain the ZIF-67 derived porous carbon / montmorillonite composite material. S2, adding an acetic acid solution into a mixed solution of polyvinyl alcohol and chitosan, quickly stirring and cross-linking, ultrasonically stirring and dispersing the composite material, and performing physical cycle freezing-melting for several times; the ZIF-67 derived porous carbon / montmorillonite composite material prepared by the invention is simple and feasible in preparation process and relatively high in photo-thermal conversion capability, formation of a complex cross-linked network of hydrogel can be promoted, the mechanical strength is obviously improved, the recycling capability, the environmental tolerance and the structural stability of the composite material are improved, and the preparation method is suitable for industrial production. Under the continuous illumination condition, the water evaporation rate can reach 2.2 kg m <-2 > h <-1 >, and the desalting capacity exceeds 98%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to a mineral-based photothermal composite hydrogel and a preparation method and application thereof. Background Art

[0002] Composite-doped hydrogel refers to a hydrogel in which one or more composite materials with unique properties are doped, and the composite materials can be evenly dispersed in the hydrogel, also known as composite hydrogel. This type of gel can exhibit some special properties, such as tensile strength, electrical conductivity, cell affinity, photothermal properties, etc. It can also improve the mechanical properties of the gel to a certain extent and is used in electrical devices, biopharmaceuticals, seawater desalination and other fields.

[0003] Photothermal materials are materials that can efficiently convert solar energy into thermal energy and are an important part of the efficient and comprehensive utilization of solar energy. Common photothermal conversion materials include metal nanoparticles, carbon-based materials and metal oxides, and their preparation methods are relatively mature. Metal nanoparticles are often prepared by chemical reduction and photochemical methods. The former reduces metal ions to nanoparticles by a reducing agent, and the latter uses photosensitizers to reduce under light. Carbon-based materials such as carbon nanotubes and graphene are mostly prepared by chemical vapor deposition and solvothermal methods. The former pyrolyzes hydrocarbon gases under the action of high-temperature catalysts, and the latter reacts in high-temperature and high-pressure solvents to generate porous carbon. Metal oxides such as iron oxide and titanium oxide are often prepared by sol-gel and hydrothermal methods. The former is prepared by hydrolysis and polycondensation of metal organic precursors, and the latter reacts in high-temperature and high-pressure aqueous solutions to generate nanoparticles. However, these preparation methods are usually accompanied by large production costs and energy consumption.

[0004] Moreover, in the prior art, photothermal materials are doped into hydrogels to form composite photothermal gels, but the composite photothermal gels in the prior art still have problems such as low strength, low light absorption rate, low evaporation rate, and high evaporation enthalpy. For example, Chinese patent CN111171340A discloses a photothermal evaporation material based on PVA hydrogel, and the evaporation rate of the PVA hydrogel photothermal evaporation material is 1.4 kg / m 2 *h. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a mineral-based photothermal composite hydrogel and a preparation method and application thereof.

[0006] A method for preparing a mineral-based photothermal composite hydrogel of the present invention comprises the following steps:

[0007] S1. Preparation of ZIF-67 derived porous carbon / montmorillonite composites

[0008] An appropriate amount of montmorillonite, cobalt nitrate hexahydrate and 2-methylimidazole are placed in a methanol solution to in-situ grow ZIF-67 particles on the surface of montmorillonite; the composite material is then calcined and carbonized to obtain a ZIF-67-derived porous carbon / montmorillonite composite material;

[0009] S2. Preparation of photothermal water gel

[0010] Acetic acid solution was added to the mixed solution of polyvinyl alcohol and chitosan, and the ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by ultrasonic stirring after rapid stirring and cross-linking. Finally, the solution was poured into a mold and subjected to physical cycle freezing-thawing for several times.

[0011] Furthermore, the mass ratio of montmorillonite, cobalt nitrate hexahydrate and 2-methylimidazole is 1-3:1:1.

[0012] Furthermore, the calcination carbonization temperature is 550-950°C and the time is 2-4h.

[0013] Furthermore, the heating rate of calcination and carbonization is 10°C / min.

[0014] Furthermore, in step S2, the mass of the ZIF-67 derived porous carbon / montmorillonite is 1-4 wt % of the total mass of the solution.

[0015] Furthermore, the mass ratio of ZIF-67 derived porous carbon / montmorillonite, polyvinyl alcohol and chitosan is 1-3:1-2:3-4.

[0016] Furthermore, the number of freeze-thaw cycles was 3 times.

[0017] Further, the concentration of the acetic acid solution is 1 wt %.

[0018] A mineral-based photothermal composite hydrogel prepared by the above-mentioned preparation method.

[0019] An application of the mineral-based photothermal composite hydrogel as described above in seawater desalination and sewage treatment.

[0020] Beneficial effects:

[0021] 1. The preparation process of the ZIF-67-derived porous carbon / montmorillonite composite material prepared by the present invention is simple and easy and has a high light-to-heat conversion capacity, and the absorbance is more than 90% in the full spectrum; while ensuring the stability of the absorbance, the production efficiency of the ZIF-67-derived porous carbon / montmorillonite composite material far exceeds that of the ZIF-67-derived porous carbon. After calcination, the organic ligands of ZIF-67 decompose, leaving nitrogen-doped porous carbon materials. This process will cause the quality loss and agglomeration of porous carbon, thereby affecting light absorption and production efficiency. The same mass of ZIF-67 is loaded on montmorillonite and then carbonized, which strengthens the structural regulation during the carbonization process, strengthens the dispersion of granular porous carbon, and realizes large-scale and efficient preparation.

[0022] 2. The introduction of ZIF-67-derived porous carbon / montmorillonite composite materials can promote the formation of a complex cross-linked network of hydrogels. Compared with the photothermal water gel prepared by ZIF-67-derived porous carbon, the mechanical strength is significantly improved, which improves its recycling ability, environmental tolerance and structural stability.

[0023] 3. The photothermal water gel provided by the present invention is applied to seawater desalination, and the water evaporation rate can reach 2.2 kg m under continuous illumination conditions. -2 h -1 , the desalination capacity exceeds 98%.

[0024] 4. The ZIF-67-derived porous carbon / montmorillonite composite material, polyvinyl alcohol and chitosan are reasonably proportioned to obtain a hydrogel with a stable structure and rich pore structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a photo of the ZIF-67 derived porous carbon hydrogel prepared in Comparative Example 1;

[0026] Figure 2 This is a photo of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 1;

[0027] Figure 3 The light absorption effects of ZIF-67, ZIF-67 derived porous carbon prepared in Comparative Example 1, and ZIF-67 derived porous carbon / montmorillonite prepared in Example 6;

[0028] Figure 4 The microscopic morphology of ZIF-67 and ZIF-67 derived porous carbon / montmorillonite prepared in Example 6;

[0029] Figure 5 The N2 adsorption-desorption isotherms of the ZIF-67-derived porous carbon prepared in Comparative Example 1 and the ZIF-67-derived porous carbon / montmorillonite prepared in Example 6;

[0030] Figure 6The pore size distribution of the ZIF-67 derived porous carbon prepared in Comparative Example 1 and the ZIF-67 derived porous carbon / montmorillonite prepared in Example 6;

[0031] Figure 7a and Figure 7b The microscopic morphology of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6;

[0032] Figure 8 Desalination effect of ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6;

[0033] Fig. 9 The ZIF-67 derived porous carbon hydrogel prepared in Comparative Example 1 and the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6 have the effect of reducing the evaporation enthalpy;

[0034] Fig.10 The light absorption effect of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 4 and Example 6;

[0035] Fig.11 The evaporation rate of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6 applied to seawater desalination. DETAILED DESCRIPTION

[0036] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0037] Example 1: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0038] (1) Preparation of ZIF-67-derived porous carbon / montmorillonite composite material: 1 g of cobalt nitrate hexahydrate was dissolved in 10 ml of methanol, 1 g of 2-methylimidazole was dissolved in another 40 ml of methanol, and 2 g of montmorillonite was dispersed in 50 ml of methanol. After dissolving them separately, the cobalt nitrate hexahydrate-methanol solution was dissolved and added dropwise to the montmorillonite-methanol solution. After stirring at room temperature for 1 hour, 2-methylimidazole was slowly poured into the above mixed solution in a straight line. After stirring at room temperature for 1 hour, it was allowed to stand for 24 hours to obtain a beautiful purple precipitate, which is montmorillonite / ZIF-67. Montmorillonite / ZIF-67 was placed in a tubular furnace in an argon atmosphere at a heating rate of 10°C / min and kept at 550°C for 3 hours to obtain a ZIF-67-derived porous carbon / montmorillonite composite material.

[0039] (2) Preparation of photothermal water gel: 0.80g chitosan and 2.40g polyvinyl alcohol were dispersed in a beaker containing 40ml pure water, heated at 90℃ and stirred for 3h to obtain a mixed solution. After the mixed solution was cooled to room temperature, 1wt% acetic acid solution was added, and 1wt% ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by ultrasonic stirring after rapid stirring and crosslinking for 30min. Finally, the solution was poured into an acrylic mold with a diameter of 3cm and a height of 2cm, and low-temperature solidification was performed at -25℃ for 6h, and then melted at room temperature, and repeated three times.

[0040] Example 2: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0041] (1) Preparation of ZIF-67-derived porous carbon / montmorillonite composite material: 1 g of cobalt nitrate hexahydrate was dissolved in 10 ml of methanol, 1 g of 2-methylimidazole was dissolved in another 40 ml of methanol, and 2 g of montmorillonite was dispersed in 50 ml of methanol. After dissolving them separately, the cobalt nitrate hexahydrate-methanol solution was dissolved and added dropwise to the montmorillonite-methanol solution. After stirring at room temperature for 1 hour, 2-methylimidazole was slowly poured into the above mixed solution in a straight line. After stirring at room temperature for 1 hour, it was allowed to stand for 24 hours to obtain a beautiful purple precipitate, which is montmorillonite / ZIF-67. Montmorillonite / ZIF-67 was placed in a tubular furnace in an argon atmosphere at a heating rate of 10°C / min and kept at 750°C for 3 hours to obtain a ZIF-67-derived porous carbon / montmorillonite composite material.

[0042] Step (2) is the same as in Example 1.

[0043] Example 3: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0044] (1) Preparation of ZIF-67 derived porous carbon / montmorillonite composite material: 1g of cobalt nitrate hexahydrate was dissolved in 10ml of methanol, 1g of 2-methylimidazole was dissolved in another 40ml of methanol, and 2g of montmorillonite was dispersed in 50ml of methanol. After dissolving them separately, the cobalt nitrate hexahydrate-methanol solution was dissolved and added dropwise to the montmorillonite-methanol solution. After stirring at room temperature for 1h, 2-methylimidazole was slowly poured into the above mixed solution in a straight line. After stirring at room temperature for 1h, it was allowed to stand for 24h to obtain a beautiful purple precipitate, which is montmorillonite / ZIF-67. Montmorillonite / ZIF-67 was placed in a tubular furnace in an argon atmosphere at a heating rate of 10℃ / min and kept at 950℃ for 3h to obtain a ZIF-67 derived porous carbon / montmorillonite composite material.

[0045] Step (2) is the same as in Example 1.

[0046] Example 4: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0047] Step (1) is the same as in Example 2.

[0048] (2) Preparation of photothermal water gel: 0.80g chitosan and 2.40g polyvinyl alcohol were dispersed in a beaker containing 40ml pure water, heated at 90℃ and stirred for 3h to obtain a mixed solution. After the mixed solution was cooled to room temperature, 1wt% acetic acid solution was added, and 2wt% ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by ultrasonic stirring after rapid stirring and crosslinking for 30min. Finally, the solution was poured into an acrylic mold with a diameter of 3cm and a height of 2cm, and low-temperature solidification was performed at -25℃ for 6h, and then melted at room temperature, and repeated three times.

[0049] Example 5: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0050] Step (1) is the same as in Example 2.

[0051] (2) Preparation of photothermal water gel: 0.80g chitosan and 2.40g polyvinyl alcohol were dispersed in a beaker containing 40ml pure water, heated at 90℃ and stirred for 3h to obtain a mixed solution. After the mixed solution was cooled to room temperature, 1wt% acetic acid solution was added, and 3wt% ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by rapid stirring and crosslinking for 30min. Finally, the solution was poured into an acrylic mold with a diameter of 3cm and a height of 2cm, and low-temperature solidification was performed at -25℃ for 6h, and then melted at room temperature, and repeated three times.

[0052] Example 6: Preparation of ZIF-67 derived porous carbon / montmorillonite hydrogel

[0053] Step (1) is the same as in Example 2.

[0054] (2) Preparation of photothermal water gel: 0.80g chitosan and 2.40g polyvinyl alcohol were dispersed in a beaker containing 40ml pure water, heated at 90℃ and stirred for 3h to obtain a mixed solution. After the mixed solution was cooled to room temperature, 1wt% acetic acid solution was added, and 4wt% ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by ultrasonic stirring after rapid stirring and crosslinking for 30min. Finally, the solution was poured into an acrylic mold with a diameter of 3cm and a height of 2cm, and low-temperature solidification was performed at -25℃ for 6h, and then melted at room temperature, and repeated three times.

[0055] Comparative Example 1: Preparation of ZIF-67-derived porous carbon hydrogel

[0056] (1) Preparation of ZIF-67 derived porous carbon composite material: Dissolve 1g of cobalt nitrate hexahydrate in 10ml of methanol and 1g of 2-methylimidazole in another 40ml of methanol. After dissolving separately, slowly pour 2-methylimidazole into the cobalt nitrate hexahydrate-methanol solution in a straight line, stir at room temperature for 1h and let stand for 24h to obtain a beautiful purple precipitate, which is ZIF-67. Place ZIF-67 in a tube furnace with an argon atmosphere at a heating rate of 10℃ / min and keep at 750℃ for 3h to obtain ZIF-67 derived porous carbon.

[0057] (2) Preparation of photothermal water gel: 0.80 g chitosan and 2.40 g polyvinyl alcohol were dispersed in a beaker containing 40 ml pure water, and heated at 90 ° C for 3 h to obtain a mixed solution. After the mixed solution was cooled to room temperature, 1 wt% acetic acid solution was added, and 4 wt% ZIF-67 derived porous carbon was dispersed by rapid stirring and cross-linking for 30 min. Finally, the solution was poured into an acrylic mold with a diameter of 3 cm and a height of 2 cm, and low-temperature solidification was performed at -25 ° C for 6 h, and then melted at room temperature, and repeated three times.

[0058] Figure 1 This is a photo of the ZIF-67 derived porous carbon hydrogel prepared in Comparative Example 1. As can be seen from the figure, the mechanical strength is low, and the surface of the hydrogel is not smooth enough after demolding and surface damage occurs.

[0059] Figure 2 This is a photo of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6; due to the introduction of the ZIF-67 derived porous carbon / montmorillonite composite material, the cross-linking sites of the polymer long chains are enriched, and the ZIF-67 derived porous carbon / montmorillonite composite material has strong mechanical stability. The two work synergistically to improve the cross-linking density and mechanical strength. After demolding, the hydrogel surface is smooth and the structure is intact.

[0060] Figure 3 The light absorption effect of ZIF-67, ZIF-67 derived porous carbon prepared in comparative example 1, and ZIF-67 derived porous carbon / montmorillonite prepared in example 6. After ZIF-67 is calcined into porous carbon, the light absorption capacity is significantly improved. According to the illustration, after ZIF-67 is loaded on MMT and calcined, the light absorption rate is also improved. It is due to the microscopic regulation of porous carbon by MMT, which changes the absorption and scattering of light and improves the light absorption rate. The absorbance is more than 90% in the full spectrum.

[0061] Figure 4 The microscopic morphology of ZIF-67 and ZIF-67-derived porous carbon / montmorillonite prepared in Example 6; ZIF-67 presents an agglomerated cubic morphology, and presents a separated porous spherical carbon morphology after composite calcination with montmorillonite.

[0062] Figure 5N2 adsorption-desorption isotherms of ZIF-67-derived porous carbon prepared in Comparative Example 1 and ZIF-67-derived porous carbon / montmorillonite prepared in Example 6; the specific surface area of ​​ZIF-67-derived porous carbon / montmorillonite is higher than that of ZIF-67-derived porous carbon.

[0063] Figure 6 The pore size distributions of the ZIF-67 derived porous carbon prepared in Comparative Example 1 and the ZIF-67 derived porous carbon / montmorillonite prepared in Example 6; the ZIF-67 derived porous carbon / montmorillonite has a richer pore structure than the ZIF-67 derived porous carbon.

[0064] Figure 7a and Figure 7b This is the microscopic morphology of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6. The ZIF-67 derived porous carbon / montmorillonite hydrogel presents a porous network structure.

[0065] Desalinated seawater ion concentration test: The hydrogel was placed between a transparent glass cover and a transparent glass plate, and 1 mL of distilled water desalinated in step (5) and 1 mL of undesalinated seawater were collected for inductively coupled plasma atomic emission spectrometry test. The ions measured were Na + , K + , Ca 2+ Mg 2+ .

[0066] Figure 8 Desalination effect of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6; the ZIF-67 derived porous carbon / montmorillonite hydrogel was applied to interface evaporation desalination of seawater. By collecting the distilled water during the desalination process, it was proved that the hydrogel can effectively remove metal ions in seawater (seawater from the Yellow Sea), with a metal ion interception rate of up to 98% and a desalination capacity of over 98%.

[0067] Fig. 9 The ZIF-67 derived porous carbon hydrogel prepared in Comparative Example 1 and the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6 have the effect of reducing the evaporation enthalpy; the ZIF-67 derived porous carbon / montmorillonite hydrogel (MMT / ZIF-67-CH) is applied to the interface evaporation desalination of seawater, which can effectively reduce the evaporation enthalpy value to 1360 J / g.

[0068] Fig.10 The light reflection effect of ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 4 and Example 6 is shown in FIG. Fig.10 It can be seen that the ZIF-67 derived porous carbon / montmorillonite hydrogel has low light reflectivity and good photothermal effect.

[0069] Water evaporation capacity test: The hydrogel was placed in a beaker of fresh water, a xenon lamp was used as the solar light source, an optical power meter was used to measure the solar energy functional density, and an electronic balance was used to monitor the mass change of water during solar-driven evaporation. The ambient temperature and humidity were 26°C and 50%, respectively. Fig.11 The evaporation rate of the ZIF-67 derived porous carbon / montmorillonite hydrogel prepared in Example 6 for seawater desalination is as follows: Fig.11 As shown in Figure 2, under continuous sunlight, the water evaporation rate can reach 2.2 kg m -2 h -1 .

[0070] For matters not mentioned above, the prior art applies.

[0071] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a mineral-based photothermal composite hydrogel, characterized in that: The steps include: S1. Preparation of ZIF-67 derived porous carbon / montmorillonite composites An appropriate amount of montmorillonite, cobalt nitrate hexahydrate and 2-methylimidazole are placed in a methanol solution to in-situ grow ZIF-67 particles on the surface of montmorillonite; the composite material is then calcined and carbonized to obtain a ZIF-67-derived porous carbon / montmorillonite composite material; S2. Preparation of photothermal water gel Acetic acid solution was added to the mixed solution of polyvinyl alcohol and chitosan, and the ZIF-67 derived porous carbon / montmorillonite composite material was dispersed by ultrasonic stirring after rapid stirring and cross-linking. Finally, the solution was poured into a mold and subjected to physical cycle freezing-thawing for several times.

2. The preparation method according to claim 1, characterized in that The mass ratio of montmorillonite, cobalt nitrate hexahydrate and 2-methylimidazole is 1-3:1:

1.

3. The preparation method according to claim 1, characterized in that: The calcination carbonization temperature is 550-950°C and the time is 2-4h.

4. The preparation method according to claim 1, characterized in that: The heating rate of calcination and carbonization was 10°C / min.

5. The preparation method according to claim 1, characterized in that: In step S2, the mass of ZIF-67 derived porous carbon / montmorillonite is 1-4 wt% of the total mass of the solution.

6. The preparation method according to claim 5, characterized in that: The mass ratio of ZIF-67 derived porous carbon / montmorillonite, polyvinyl alcohol and chitosan is 1-3:1-2:3-4.

7. The preparation method according to claim 1, characterized in that: The number of freeze-thaw cycles was 3 times.

8. The preparation method according to claim 1, characterized in that: The concentration of the acetic acid solution was 1 wt%.

9. A mineral-based photothermal composite hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the mineral-based photothermal composite hydrogel as claimed in claim 9 in desalination of seawater and sewage treatment.

Citation Information

Patent Citations

  • PVA hydrogel-based photo-thermal evaporation material and preparation and application thereof

    CN111171340A

  • Preparation method of boron-doped porous carbon rod-like material

    CN115196617A

  • Cobalt-doped flower-like montmorillonite composite material and preparation method and application thereof

    CN115642239A

  • Porous carbon hydrogels for efficient solar interface evaporation

    CN116712939A

  • Photothermal conversion mineral material as well as preparation method and application thereof

    CN117285379A